A tutela coletiva ambiental e seus instrumentos como garantia do meio ambiente ecologicamente equilibrado - Held, Thaisa Maira Rodrigues (2013)
The environment is the theme of remote discussions, whether at international conferences, whether through domestic legislation of the States, albeit very superficial, given the consequences of human action on it. This issue gained momentum at the approach to human rights. Even though it is a fundamental human right, it should understand is a the right to life in all its forms. The State, as well as the whole society, has a duty to protect and preserve the ecological balance so intergenerational. It is in this endeavor that one should resort to hedging instruments, whether preventive or repressive, judicial or extrajudicial. The key point of this research refers to the legal instruments for environment protection, this is a right that the transcendent individual. The procedural issue has always been guided by individual labors, resulting from the traditional model brought by the State Liberal Law. However, given the need to effect the trans rights guarantees and the failure of individual system of conflict resolution, models were created, both in the international sphere, as in Brazil, guardianships and collective realization of these rights. It is in this setting that the right to an ecologically balanced environment fits perfectly with the possibility of participation of all, a framework instrument with its own peculiarities, but they have one common feature either, the realization of balanced environmental protection to all, indistinctly, so intergenerational justice in the ideal environment.